Utilization of Biotechnology on Some Forest Trees in Turkey - Yer, Esra Nurten; Ayan, Sezgin (Hrvatski Sumarski Institut (Croatian Forest Research), 2014)
Background and Purpose: Raw wood material requirements are increasing with rapid population growth both in Turkey and in the world. In order to supply deficit for closure of forest products, productivity and quality of production should be improved. Basic ways to increase efficiency in forest production involves silvicultural implementations and classical tree breeding studies. Genetic variation can be increased by utilizing the existing diversity. Thus, new combinations can be obtained and we can raise efficiency using some selection strategies. At this point, biotechnological methods are required to meet the genetic material. Studies of forest tree breeding are a slow process due to the size of the genome and the length of the tree life span. Biotechnological applications in forest trees provide many important benefits in terms of time saving and reducing cost when compared to classical breeding studies. Sustainable forestry practices are gaining rapid acceleration via biotechnology and modern sciences practices. In this study, for some forest tree species in Turkey, the evaluated biotechnology methods included; 1- tissue culture and clonal propagation, 2- molecular marker applications, 3- marker assisted selection and breeding, 4-genomic and proteomic studies, 5- genetic modification and genetic engineering applications. Conclusions: In this study, the works were carried out on forest tree breeding/propagation in Turkey and it was mainly focused on vegetative production techniques with 25 broadleaves and 9 conifer taxa, which were possible to express. Molecular genetic studies were carried out on 12 broad leaves taxa and 9 conifer taxa; genetic transformation studies were conducted on poplar species. Thus, it might be suggested that a combination of biotechnological tools and traditional propagation methods will ensure advantage for the development of forest-tree species.
Keywords: sustainable forestry; genomics studies; Forestry; tree breeding; tissue culture; SD1-669.5; biotechnology; 2. Zero hunger; 15. Life on land; 12. Responsible consumption